IDENTIFYING AFFIXES USED IN THE 18th TO 19th CENTURY CLASSIC SHORT STORIES - Rindi Fediany; Lilia Indriani (Universitas Galuh, 2021)
Affix is a term that cannot be separated from linguistic. It is a grammatical element attached to a word, stem, or phrase to produce derived or inflected forms. Affixes can be distinguished into three types, namely prefix, infix, and suffix. Infix is a letter or a stem of words inserted into the root itself, and a prefix is a letter or group of letters that is added or placed before the stem of a word, while a suffix is placed at the end of the stem of a word. Affixes consist of three types. There are prefixes, infixes, and suffixes. This study aims to determine what types of affixes were used in the 18th to 19th century classic short stories and which type was used the most. This study is a descriptive qualitative method, and this study uses documentation and observation methods to get the data. Then the data is analyzed by identifying words containing affixes found in those short stories. The data analysis is used to conclude. The result of the analysis shows which affixes were used the most.